Successful Treatment of Kaposi Sarcoma–Associated Herpesvirus Inflammatory Cytokine Syndrome After Kidney–Liver Transplant: Correlations With the Human Herpesvirus 8 miRNome and Specific T Cell Response. Issue 11 (27th June 2017) - Mularoni, A.; Gallo, A.; Riva, G.; Barozzi, P.; Miele, M.; Cardinale, G.; Vizzini, G.; Volpes, R.; Grossi, P.; Di Carlo, D.; Luca, A.; Trenti, T.; et al.
Abstract : After transplant, patient infection with human herpesvirus 8 (HHV‐8) and Kaposi sarcoma–associated herpesvirus (KSHV) is known to cause aggressive tumors and severe nonneoplastic complications. These latter syndromes are driven by HHV‐8/KSHV lytic reactivations and related hyperinflammatory host responses typically characterized by high viral loads, elevated levels of cytokines and other inflammation biomarkers, cytopenia, organ failure, high fever, and worsening conditions (with no evidence of B cell neoplasias). These disorders are associated with a high mortality rate, often due to lack of prompt diagnosis, effective therapeutic approaches, and adequate follow‐up. These features resemble most of those defining the so‐called KSHV‐associated inflammatory cytokine syndrome (KICS), which was recently recognized in patients positive for human immunodeficiency virus (HIV). In this report, we describe—for the first time—a case of a KICS‐like nonneoplastic recurrent complication occurring after transplant in an HIV‐negative patient that was successfully treated by a combination of anti‐CD20 monoclonal therapy, antivirals, and modification of the immunosuppressive regimen. In addition to clinical and laboratory findings collected during 3‐year follow‐up, we report novel experimental data on HHV‐8–specific T cell dynamics and circulating microRNA profile, showing correlations with clinical course and other laboratory markers (including viral load, C‐reactive protein, and cytokine levels), providing useful information about abnormal cellular and cytokine dynamics underlying HHV‐8–associated inflammatory disorders in posttransplant patients. Abstract : The authors report the first case of successful treatment of Kaposi sarcoma herpesvirus inflammatory cytokine syndrome occurring in a kidney–liver transplant patient secondary to donor‐derived HHV‐8 infection together with experimental data regarding HHV‐8–specific T cell dynamics and circulating miRNA profile.